Untreated HIV-1 infection and low CD4+ T cell counts and their effect on endemic human coronavirus (re)infection. - Ferdyansyah Sechan; Anne W M van den Hurk; T Sonia Boender; Maria Prins; Amy Matser; Margreet Bakker; Neeltje A Kootstra; Lia van der Hoek (PLOS Global Public Health)
People living with HIV-1 (PLWH) treated with combination antiretroviral therapy (cART) have similar incidence of SARS-CoV-2 infection compared to people without HIV-1 (PWoH). Yet, roughly 25% PLWH worldwide are currently not accessing cART. The influence of CD4+ T cell depletion on human coronavirus (HCoV) (re)infection risk, including SARS-CoV-2, is largely unknown. In this research, we investigated the incidence of infection by the four endemic HCoVs (HCoV-NL63, HCoV-229E, HCoV-OC43, and HCoV-HKU1), to inform on future reinfections by SARS-CoV-2. We compared the HCoV infection incidence rate between PLWH (n = 24) and PWoH (n = 25) who were followed up in 1984-1993; i.e., before cART became generally available in high income countries. Both populations were followed up at 6-month intervals for 7 or 8 years. We also compared the HCoV infection incidence rate among PLWH with and without immune deficiency, defined as CD4+ T cell count < 350 cell/mm3 and > 350 cell/mm3 respectively. We found that the antibody levels for all HCoVs were significantly lower in PLWH than PWoH across all timepoints. However, we observed no significant difference on HCoV infection incidence rate between PLWH and PWoH. We also observed no difference in HCoV infection incidence rate among PLWH with and without immune deficiency. We conclude that PLWH not on cART may not be at increased risk of HCoV reinfections.